The Effect of Career Development on Organizational Citizenship Behavior Mediated By Employee Engagement - Ni Kadek Vera Dwi Ocktaviani; Made Surya Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of career development on organizational citizenship behavior (OCB), mediated by employee engagement, with a case study at Prama Sanur Beach Bali. A saturated sampling technique was used, with the total population of 104 employees serving as the sample. The research method employed was a survey using questionnaires and interviews, analyzed through descriptive statistics and inferential statistical tools using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that career development has a positive and significant effect on organizational citizenship behavior. Career development also has a positive and significant effect on employee engagement. Moreover, employee engagement has a positive and significant effect on organizational citizenship behavior and mediates the relationship between career development and organizational citizenship behavior.